2012
DOI: 10.1111/j.1365-2664.2012.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Large carabid beetle declines in a United Kingdom monitoring network increases evidence for a widespread loss in insect biodiversity

Abstract: Summary1. Carabid beetles are important functional components of many terrestrial ecosystems. Here, we describe the first long-term, wide-scale and quantitative assessment of temporal changes in UK carabid communities, to inform nationwide management aimed at their conservation. 2. Multivariate and mixed models were used to assess temporal trends over a 15-year period, across eleven sites in the UK Environmental Change Network. Sites covered pasture, field margins, chalk downland, woodland and hedgerows in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(161 citation statements)
references
References 46 publications
(78 reference statements)
7
140
2
1
Order By: Relevance
“…There are already well established insect model indicator groups for monitoring landscape-wide biodiversity within these agroecosystems, including representatives for important ecosystem services such as pollination, and natural enemies of agricultural pests. These indicator groups include butterflies, moths, bees, hoverflies, and carabid beetles (Bommarco et al 2012; Brooks et al 2012; Ekroos et al 2013; Geiger et al 2010; Kremen and M'Gonigle 2015). Most of these groups of insects apparently do not use long-range pheromones that could be exploited for monitoring, they are often visually conspicuous, and/or they can be sampled reasonably well through alternative means such as manual surveys or unbaited pitfall or pan traps.…”
Section: Model Systems and Their Usefulness For Conservation Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…There are already well established insect model indicator groups for monitoring landscape-wide biodiversity within these agroecosystems, including representatives for important ecosystem services such as pollination, and natural enemies of agricultural pests. These indicator groups include butterflies, moths, bees, hoverflies, and carabid beetles (Bommarco et al 2012; Brooks et al 2012; Ekroos et al 2013; Geiger et al 2010; Kremen and M'Gonigle 2015). Most of these groups of insects apparently do not use long-range pheromones that could be exploited for monitoring, they are often visually conspicuous, and/or they can be sampled reasonably well through alternative means such as manual surveys or unbaited pitfall or pan traps.…”
Section: Model Systems and Their Usefulness For Conservation Monitoringmentioning
confidence: 99%
“…Measures to halt the decline of biodiversity often have proven ineffective (Batary et al 2015; Butchart et al 2010), which increases the need for evidence-based conservation strategies. Insects represent the most diverse group of animals, and include high numbers and proportions of threatened species (Brooks et al 2012; Conrad et al 2006). They also constitute essential components of food webs in terrestrial and aquatic ecosystems, and provide important ecosystem services such as pollination, pest control, and recycling of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…For example, carabid beetles are known to exhibit considerable annual population fluctuations (Baars and Van Dijk 1984;den Boer 1985den Boer , 1990Brooks et al 2012), presenting an alternative explanation for their observed decline in local and regional diversity. However, even if the observed diversity decline for carabid beetles is caused by annual population fluctuations rather than a decreasing trend, there is still reason for concern.…”
Section: Differences Between Taxonomic Groupsmentioning
confidence: 99%
“…Voor het bepalen van de oorzaken van trends is het nuttig om onderscheid te maken tussen in Europa is een overall-achteruitgang vastgesteld van de soortenrijkdom en/of de aantallen van bepaalde insectengroepen, waaronder dagvlinders (Thomas, Telfer et al 2004;Van Dyck, Van Strien et al 2009;Dirzo, Young et al 2014;Habel, Segerer et al 2016;Thomas, 2016, Van Swaay, Van Strien et al 2016, nachtvlinders (Conrad, Warren et al 2006;Fox 2013, Fox, Oliver et al 2014, zweefvliegen Vogel, 2017), loopkevers (Brooks, Bater et al 2012) en wilde bijen (Biesmeijer, Roberts et al 2006;Goulson, Lye et al 2008;Carvalheiro, Kunin et al 2013;Scheper, Reemer et al 2014). …”
Section: Operationele Factoren En Drukfactorenunclassified